Eyelid Spontaneous Blink Analysis and Age-Related Changes Through High-Speed Imaging. Issue 5 (September 2019) - DeAngelis, Kendra D.; Rider, Alex; Potter, Whitney; Jensen, Jason; Fowler, Brian T.; Fleming, James C.
Abstract : Purpose: To analyze the spontaneous eyelid blink and sphincter closure activity of the orbicularis oculi by measuring the horizontal eyelid movement. Methods: Individuals 18+ years of age, any ethnicity, and gender were recruited. Participants completed a questionnaire to determine eligibility. Exclusion criteria included the following: history of facial trauma, nerve palsy, surgery, use of periorbital neuromodulators or filler within the past year, thyroid eye disease, and eyelid or ocular surface disease. Data were collected from participants by decade. Eyelid blinks were recorded using the FPS 1000HD. The motions of 3 spontaneous blinks in primary gaze were recorded. All blinks were reviewed and one chosen for most accurate analysis. Horizontal palpebral fissure width and its changes of open and closed eye measurements were taken using National Institute of Health ImageJ software version 2.0. The data were subjected to SAS version 9.4 analysis using paired t test, t test, and linear models. Results: One hundred thirty-six patients were recruited. Fourteen patients were excluded; 122 patients were used in analysis. Ages ranged from 22 to 90 years. Participants were divided into 6 groups according to age (20–29, 30–39, 40–49, 50–59, 60–69, and 70+ years of age). The average horizontal fissure length across all ages was 24.23 mm. Average change in horizontal fissure length decreased 1.42 mm among all ages. There was a statistically significant difference comparing age 20–29 decade to age 70+ decade. Conclusions: Horizontal fissure length changes with eyelid blink and defines 1 component of the eyelid sphincter. Abstract : This study establishes the horizontal component of the spontaneous eyelid blink as being consistently quantifiable and introduces the concept of the orbicularis oculi muscle as the eyelid sphincter.